Change in eating‐disorder psychopathology network structure in patients with anorexia nervosa treated with intensive cognitive behavior therapy. Issue 10 (31st July 2021) - Calugi, Simona; Dametti, Laura; Chimini, Mirko; Dalle Grave, Anna; Dalle Grave, Riccardo
Abstract: Objective: This study was designed to compare the change in eating‐disorder feature networks in patients with anorexia nervosa after treatment with intensive enhanced cognitive behavior therapy (CBT‐E). Methods: Patients seeking treatment for anorexia nervosa were consecutively recruited from January 2016 to September 2020. All patients aged ≥16 years who completed a 20‐week intensive CBT‐E program (13 weeks of inpatient followed by 7 weeks of day‐hospital treatment) were included in the study. Body mass index (BMI) was measured, and the Eating Disorder Examination Questionnaire completed for each patient, both at baseline and the end of treatment. Results: The sample comprised 214 patients with anorexia nervosa. Treated patients showed significant improvements in BMI and eating‐disorder psychopathology. Network analysis revealed a significant reduction in the network global and connection strengths at the end of treatment. The most central and highly interconnected nodes in the network at baseline were related to the drive for thinness, but at the end of treatment to body image concerns. Some edge connections were significantly stronger at baseline than at the end of treatment, while others were significantly stronger at the end of treatment than at baseline. Discussion: CBT‐E reduces the psychopathology network connectivity over time in patients with anorexia nervosa. The differences in central nodes and edge connections between baseline and end of treatment, not detected by classical inferential analysis, may be informative for understanding the centrality of symptoms in the psychopathology network, and how a specific treatment may act to reduce symptoms and change their connections over time.